FAST TRACK USA REGULATORY APPROVAL FOR DRUGS TO TREAT EMERGING INFECTIOUS DISEASES: Fast track Approval - GM, PAVITHRA; MAANVIZHI, SABA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
The Food and Drug Administration has established fast track approval to speed the designation of drugs that efficiently treat serious conditions, in particular those that provide improved advantages over available therapy. Fast track designation was initiated to curtail the time period in the new drug approval procedure and to promote the drug discovery and commercialization of drug products for critical and life-threatening illness and expedite the approval of drug products demonstrating advanced efficacy toward the prevailing one. Single Phase II study is reviewed before approving the drug within fast track designation. This review article highlights the consequences, criteria for fast track designation, fast track designation process, and the timeline for fast track approval.